2016
DOI: 10.1002/cam4.758
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and survival in patients with gastric cancer

Abstract: The objective of this study is to examine the impact of marital status on incidence of metastasis at diagnosis, receipt of surgery, and cause‐specific survival (CSS) in patients with gastric cancer (GC). Research data is extracted from The Surveillance, Epidemiology, and End Results (SEER) database, and 18,196 patients diagnosed with GC from 2004 to 2010 are involved. Effects of marital status on incidence of metastasis at diagnosis, receipt of surgery, and CSS are determined using multivariable logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 43 publications
12
31
0
Order By: Relevance
“…This is in line with previous SEER analyses for pancreatic cancer patients[14] as well as for many other solid tumors[15,16]. Moreover, the current analysis showed an evidence for age and racial differences in survival outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous SEER analyses for pancreatic cancer patients[14] as well as for many other solid tumors[15,16]. Moreover, the current analysis showed an evidence for age and racial differences in survival outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Another surprising factor was that unmarried patients had a 32% reduced risk of receiving CRN. This has not been reported previously in this setting, but may reflect the observation in many cancers that married patients receive more treatment and better outcomes .…”
Section: Discussionsupporting
confidence: 45%
“…Besides, several recent studies have shown that ignoring the effects of dying from other causes, unmarried gastric cancer, especially widowed patients, have a higher risk of all-cause mortality and GCSM [52,53]. Furthermore, in another study, the authors reported that marriage had a protective effect on the undertreatment and other causes of mortality [54]. However, the results of the competing risk model show that there was no difference in GCSM of the married and unmarried patients, and the risk of the later dying from other causes is signi cantly higher than the former.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the contradiction between GCSM and all-cause mortality mainly aroused from the higher risk of competing events in unmarried gastric cancer. Furthermore, married patients who bene ted from their spouse's support and care may reduce side effect on the survival from other diseases and improve the survival rate of gastric cancer [54].…”
Section: Discussionmentioning
confidence: 99%